Non-surgical treatment alternatives of mandibular fractures in pediatric patients - Muñante-Cárdenas, José (2008)
Facial traumas in pediatric patients show considerations that are not present in adults, related to prevalence, diagnosis and treatment. Facial fractures prevalence in children is low, ranging from 13 to 15%. This can be due to anatomic or environmental factors, such as traffic accidents, falls and sport accidents as the main ones. The choice of treatment alternative will depend on the intrinsic characteristics of the fracture, the patient’s age and teeth development stage. Thus heterogeneity along with low incidence of facial fracture in pediatric patients, and limited experience of some clinical and surgical professionals in child trauma management can be support for lack of consensus in treatment. Generally, minor age of patient have more conservative management. Fractures with minimum displacement can be treated in a conservative way, by means of máxilo mandibular fixation, observation, soft diet and rest or analgesic medication when necessary. The open reduction with rigid internal fixation should be performed only in cases of moderate to severe bone displacement.